Red ginseng powder fermented with probiotics exerts antidiabetic effects in the streptozotocin-induced mouse diabetes model. (1st January 2017) - Jang, Sun-Hee; Park, Jisang; Kim, Sae-Hae; Choi, Kyung-Min; Ko, Eun-Sil; Cha, Jeong-Dan; Lee, Young-Ran; Jang, Hyonseok; Jang, Yong-Suk
Abstract: Context: Red ginseng (heat-processed Panax ginseng ) is a well-known alternative medicine with pharmacological antidiabetic activity. It exerts pharmacological effects through the transformation of saponin into metabolites by the intestinal microbiota. Given that intestinal conditions and intestinal microflora vary among individuals, the pharmacological effects of orally administered red ginseng likely may vary among individuals. Objective: To overcome this variation and produce homogeneously effective red ginseng, we evaluated the antidiabetic effects of probiotic-fermented red ginseng in a mouse model. Materials and methods: The antidiabetic efficacy of orally administered probiotic-fermented red ginseng was assessed in ICR mice after induction of diabetes using streptozotocin (170 mg/kg body weight). Samples were given orally for 8 weeks, and indicators involved in diabetic disorders such as body weight change, water intake, blood glucose, glucose tolerance and various biochemical parameters were determined. Results: Oral administration of probiotic-fermented red ginseng significantly decreased the level of blood glucose of about 62.5% in the fasting state and induced a significant increase in glucose tolerance of about 10.2% compared to the control diabetic mice. Additionally, various indicators of diabetes and biochemical data (e.g., blood glycosylated haemoglobin level, serum concentrations of insulin, and α-amylase activity) showed a significant improvement in the diabetic conditions of the mice treated with probiotic-fermented red ginseng in comparison with those of control diabetic mice. Discussion and conclusion: Our results demonstrate the antidiabetic effects of probiotic-fermented red ginseng in the streptozotocin-induced mouse diabetes model and suggest that probiotic-fermented red ginseng may be a uniformly effective red ginseng product.